Reading Interest Profile of Fourth-Grade Students at SDIT Insan Rabbani as a Basis for Developing Culturally Responsive Digital Storybooks - Febriyanto, Budi; Sunendar, Dadang; Musthafa, Bachrudin; Yansyah, Jepri; Yamusanor, Aiman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This descriptive quantitative study examined the reading interest profile of fourth-grade students at SDIT Insan Rabbani, Majalengka Regency, Indonesia, as a needs analysis for developing culturally responsive digital storybooks. The study aimed to identify students' reading interest across five indicators adapted from Burns and Lowe to provide an empirical basis for literacy-oriented instructional media. Method: The study involved all 34 fourth-grade students using a total sampling technique. Data were collected through a structured questionnaire measuring five indicators of reading interest: (1) need for reading materials, (2) efforts to seek reading materials, (3) enjoyment of reading, (4) desire to read continuously, and (5) follow-up actions after reading. The questionnaire was validated through expert judgment (CVI = 0.94) and demonstrated high internal consistency (Cronbach's α = 0.89). Data were analysed using descriptive statistics by calculating the mean score for each indicator. Results: The findings revealed a moderate-to-low and uneven reading interest profile. The highest mean score was obtained for the need for reading materials (75.42), while the lowest score was found for the desire to read continuously (65.36). Lower scores were also identified for efforts to seek reading materials (68.68) and follow-up actions after reading (68.17), indicating that students recognised the importance of reading but had not yet developed consistent, autonomous, and reflective reading habits. Novelty: This study contributes by providing an empirical reading interest profile that serves as a foundation for developing culturally responsive digital storybooks incorporating local wisdom, including local folklore, Sundanese cultural values, audio narration, interactive illustrations, vocabulary support, comprehension activities, and post-reading retelling tasks to enhance literacy engagement among elementary school students.